THE INFLUENCE OF HUMAN RESOURCES DEVELOPMENT, POSITIONING, MOTIVATION AND WORK DISCIPLINE ON THE PERFORMANCE OF THE STATE CIVIL APPARATUS AT THE FINANCIAL ASSET MANAGEMENT REGIONAL OFFICE OF PAPUA PROVINCE - Yolanda Pouw; H. Muhdi B. Hi Ibrahim (Universitas Yapis Papua, 2022)
This study was aimed at determining the development of human resources, placement (positioning), motivation and work discipline on the performance of the state civil apparatus at the office of the regional financial and asset management agency (BPKAD) of Papua province. Samples were taken using a purposive sampling method with a total sample of 140 respondents. The analytical method used is multiple linear regression. The results show that organizational climate and job satisfaction had a positive and significant effect on employee performance at the financial and asset management regional agency (BPKAD) of Papua Province. Work discipline has a negative and significant effect on officer’s performance at the regional financial and asset management agency (BPKAD) of Papua Province. Motivation has no effect and no significant effect on officer’s performance at the regional financial and asset management agency (BPKAD) of Papua Province